Ketidaklayakan Pembentukan Peraturan Pemerintah Pengganti Undang-Undang dengan Metode Omnibus Law - Kishan, Marcelino Ceasar; Yanto, Oliviani; Jeconiah, Bernadeta Adriana Sandra (Fakultas Hukum Universitas Udayana, 2024)
This article discusses the government’s acrobatics in forming the Government Regulation in Lieu of Law (as known as Perppu) using the omnibus law method which has caused controversy. The studied aspect is the feasibility of Perppu to be able to use the omnibus law method. Looking further, Law Number 13 of 2022 on the Second Amendment to Law Number 12 of 2011 on The Establishment of Laws and Regulations has restrained the use of omnibus law method in forming laws with the necessity to enact through planning documents. Based on the Legal Restraint perspective, this article is in a negative position to legitimize the use of the omnibus law method in Perppu. The rationalization is because Perppu was formed without using planning documents and it cannot take refuge in an emergency clause which obliges it to grant unlimited exceptions. The force to form Perppu using the omnibus law method is a form of a Constitutional Dictatorship that also in the process of enacting it has the potential to create constitutional chaos. In elaborating the legal issue, the research method used in this article is normative legal research with statutory approaches, conceptual approaches, comparative approaches, and historical approaches.